Intravenous Therapy for Chronic Pulmonary Aspergillosis: A Systematic Review and Meta-analysis - Bongomin, Felix; Asio, Lucy Grace; Olum, Ronald; Denning, David W. (Mycoses, 2020)
Chronic pulmonary aspergillosis (CPA) is a potentially life-threatening debilitating lung disease necessitating long-term oral antifungal treatment. However, development of antifungal resistant isolates of Aspergillus and major toxicities requiring discontinuation of treatment limit their use. Intravenous (IV) antifungals are an option in this group of patients. We comprehensively evaluate the response rates to IV antifungals in the management of CPA. We searched Medline and Embase databases to select clinical studies providing information about IV amphotericin B or an echinocandin for the treatment of CPA from inception to May 2020. Reviews, single case reports and case series reporting less than 10 patients were excluded. We evaluated 12 eligible studies. A total of 380 patients received amphotericin B (n =143) or an echinocandin (n=237) and were included in the meta-analysis. In a pooled analysis, overall response to IV antifungals was 61% ((95% confidence interval (CI): 52-70%; I2=73.3%; p<0.001), to amphotericin B was 58% (95% CI: 36-80%; I2=86.6%; p<0.001) and to echinocandins was 62% (95% CI: 53-72%; I2=63.6%; p<0.001). Amphotericin B courses were usually doses at slightly less that 1mg/Kg (deoxycholate) or 3mg/Kg (liposomal) for 2-3 weeks. Micafungin doses varied from 12.5 to 300mg (frequently, 150mg) daily for at least 3 weeks, and sometimes much longer. Liposomal amphotericin B was well tolerated, but led to renal function loss in 25% of patients. Adverse events were observed in 5 – 35.3% of patients receiving echinocandins, none of which was considered major. Intravenous antifungals have a place in the management of CPA. A head-to-head comparison of amphotericin B and echinocandins is lacking, and future studies should look at evaluating short and longer-term outcomes of these agents.
Keywords: Chronic pulmonary aspergillosis; Amphotericin; Micafungin; Caspofungin; Anidulafungin; Aspergillus